The Iban Textiles - Alexander, Chelum; Anna, Durin; Lim, Connie Keh Nie; Muhammad Qawiem, Hamizan; Mohd Jefri, Samaroon (UNIMAS Publisher, 2018)
The Iban traditional textiles are very well decorated with beautiful motifs. Some motifs are small and simple but some are complex (Durin, 2011). Both the simple and complex motifs are embedded meaning and symbols which depict the Iban traditional culture especially their traditional beliefs. This research aims to relate the motif of the I ban Textile and their tradisional belief. Secondly, this research is also to analyse the usage of Pua Kumbu traditionally and currently. The data collection are carried out through observation and interviewing the experts in Iban textiles weaving in Kuching, Betong and Bintulu. The analysis method is used for the data collection is content analysis. In the research finding it is proven that the usage Pua Kumbu currently is not only confined to ritual purposes but also for the daily used as decorative accessories. It's also proven, not only the Iban community weave the Pua Kumbu but few communities also weave the Iban's textile motif. For example, Azmeer Sharkawi in Betong